Bedtime procrastination: A self-regulation perspective on sleep insufficiency in the general population. (May 2016) - Kroese, Floor M; Evers, Catharine; Adriaanse, Marieke A; de Ridder, Denise TD
Getting insufficient sleep has serious consequences in terms of mental and physical health. The current study is the first to approach insufficient sleep from a self-regulation perspective by investigating the phenomenon of bedtime procrastination : going to bed later than intended, without having external reasons for doing so. Data from a representative sample of Dutch adults ( N = 2431) revealed that a large proportion of the general population experiences getting insufficient sleep and regularly goes to bed later than they would like to. Most importantly, a relationship between self-regulation and experienced insufficient sleep was found, which was mediated by bedtime procrastination.